Artificial stone raw material and preparation method thereof, artificial stone product prepared therefrom and application thereof

By combining glass fiber composite aluminum hydroxide powder with unsaturated polyester, the problem of high thermal expansion coefficient of artificial stone is solved, the crack resistance is improved, the preparation process is simplified and the cost is reduced, and the application range of artificial stone products is expanded. .

CN116283062BActive Publication Date: 2025-01-10JOMOO KITCHEN & BATHROOM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310265250.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-01-10
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The problems of existing artificial stone products with high thermal expansion coefficient and poor deformation resistance in large size or special-shaped applications limit their application in kitchen and bathroom countertops, and the existing modification methods are complex and costly.

Method used

Using glass fiber composite aluminum hydroxide powder, aluminium hydroxide-covered glass fiber composite powder is prepared by mixing glass fiber and aluminum ion solution in an alkaline environment, and after heating, stirring, suction filtration and drying, the aluminum hydroxide-covered glass fiber composite powder is prepared and combined with Unsaturated polyester compound reduces the thermal expansion coefficient of artificial stone.

Benefits of technology

It significantly reduces the thermal expansion coefficient of artificial stone, improves crack resistance, simplifies the preparation process, reduces production costs, and expands the application range of artificial stone products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116283062B_ABST
    Figure CN116283062B_ABST
Patent Text Reader

Abstract

A glass fiber composite aluminum hydroxide powder and a preparation method thereof, an artificial stone prepared thereby and a preparation method and application thereof. In the glass fiber composite aluminum hydroxide powder, by mass, the glass fiber: aluminum hydroxide is 10:1-1:6; the artificial stone, by mass, includes the following components in percentage by mass: 20-40% unsaturated polyester, 50-75% glass fiber composite aluminum hydroxide powder, 0.5-2% curing agent, 0.5-2% accelerator, 0.1-2% defoaming agent, and 1-3% color paste. The artificial stone product prepared by the method of the present application can reduce the thermal expansion coefficient of the artificial stone to ensure the long-term anti-deformation and anti-cracking performance of the artificial stone product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building decoration and decorative materials, and in particular to a glass fiber composite aluminum hydroxide powder and a preparation method thereof, and artificial stone prepared therefrom and a preparation method and application thereof. Background Art

[0002] In the field of building decoration materials, artificial stone is welcomed by the market due to its unique advantages, such as reproducibility, easy processing, no color difference, etc. It occupies an important position in the decoration industry, especially in the field of kitchen and bathroom countertops. The artificial stone industry is an energy-saving and environmentally friendly industry that turns waste into treasure and recycles resources. The industry makes full use of various low-value waste stone resources. The production process does not require a large amount of fuel consumption and has no waste gas emissions. It has become an important direction for the development of the decorative stone industry. Artificial stone is mainly made of unsaturated polyester resin as a bonding material, natural stone fragments or calcium carbonate powder, aluminum hydroxide powder, silica powder and other inorganic fillers, and then added with pigments and a small amount of initiator. It is processed through stirring, mixing, condensation and curing. The main products are solid surface material artificial stone, artificial quartz stone, artificial granite, etc. Due to the large shrinkage of unsaturated polyester resin, artificial stone has a larger thermal expansion coefficient compared to natural stone or ceramic products, which leads to serious challenges to the dimensional stability, deformation resistance and long-term resistance to sudden cooling and heating of artificial stone, which seriously limits the application of artificial stone products in large-sized or special-shaped products. How to reduce the thermal expansion coefficient of artificial stone to ensure the long-term deformation resistance and cracking resistance of artificial stone products, expand the application range of artificial stone products, and promote the development of the artificial stone industry is of great significance. To this end, some patents have been published:

[0003] 1. As in CN201410629239.5, unsaturated polyester is modified by using alkaline earth metal oxide / hydroxide, and then the modified unsaturated polyester is used as a binder to prepare artificial stone, thereby achieving the effect of reducing the thermal expansion coefficient α of the artificial stone and increasing the thermal transition point Tt at the same time.

[0004] 2. As in patent CN202110889101.9, bamboo strips are used as raw materials, and steam explosion fibers are obtained by defibrination through steam explosion to obtain steam-exploded fibers rich in hydroxyl groups on the surface. The steam-exploded fibers are then subjected to surface corona treatment to obtain modified fibers. The modified fibers are then used as templates, and calcium sulfate whiskers are deposited on their surface to obtain fibrous calcium sulfate whiskers. Then, sodium silicate and hydrochloric acid are reacted to produce orthosilicic acid precipitates that adhere to the surface of the fibrous calcium sulfate whiskers. The precipitates are then hydrolyzed under high temperature and high pressure to produce nano-silicon dioxide that is coated on the surface of the fibrous calcium sulfate whiskers to obtain silicon-coated modified fibrous calcium sulfate whiskers, which are used as artificial marble fillers and compounded with unsaturated polyester matrix, and cured under the action of a curing agent to finally produce anti-fouling and anti-cracking artificial marble.

[0005] However, the above patents have the following problems:

[0006] 1. Modifying unsaturated polyester with alkaline earth metal oxides / hydroxides and using it as a binder for artificial stone can indeed reduce the expansion coefficient α of artificial stone. However, the introduction of alkaline earth oxides / hydroxides into the artificial stone system will inevitably affect the corrosion resistance of the artificial stone products and have an adverse effect on the long-term stability of artificial stone products.

[0007] 2. By using modified fibers as a matrix and obtaining silicon-coated modified fibrous calcium sulfate whiskers through multiple deposition reactions as artificial stone fillers and compounding them with unsaturated polyester matrix, anti-fouling and anti-cracking artificial marble products are obtained. The preparation process of the filler is very complicated and cumbersome, and requires multiple high-temperature and high-pressure treatments. The production cost is too high, making it difficult to promote it on a large scale as a daily necessity.

[0008] Therefore, there is an urgent need in the art for a method for preparing artificial stone, which can reduce the thermal expansion coefficient of the artificial stone to ensure the long-term anti-deformation and anti-cracking performance of the artificial stone product. Summary of the invention

[0009] The present application provides an artificial stone raw material and a preparation method thereof, an artificial stone product prepared thereby, and a preparation method and application thereof, wherein the artificial stone raw material is glass fiber composite aluminum hydroxide powder. The artificial stone product prepared from the glass fiber composite aluminum hydroxide powder can reduce the expansion coefficient of the artificial stone and improve the crack resistance of the artificial stone.

[0010] The present application provides a glass fiber composite aluminum hydroxide powder, wherein the ratio of glass fiber to aluminum hydroxide is 10:1-1:6 by mass.

[0011] In an exemplary embodiment, the length of the glass fiber is 0.1 mm-6 mm.

[0012] The present application provides a method for preparing glass fiber composite aluminum hydroxide powder, comprising mixing a glass fiber solution and an aluminum ion solution in an alkaline environment, and obtaining the glass fiber composite aluminum hydroxide powder after heating, stirring, filtering and drying.

[0013] In an exemplary embodiment, the preparation method includes: i) adding the glass fiber to deionized water and stirring to obtain a uniformly dispersed glass fiber solution; ii) adjusting the pH of the glass fiber solution to make it alkaline; iii) adding an aluminum ion solution to the glass fiber solution under high-speed stirring to obtain a mixed solution, heating and continuously stirring, while continuing to adjust the pH to be greater than 7; iv) filtering and drying the mixed solution to obtain the glass fiber composite aluminum hydroxide powder.

[0014] In an exemplary embodiment, in step ii), an alkaline substance is added to the glass fiber solution to make the pH of the glass fiber solution be 8-12, and the alkaline substance is ammonia water, sodium hydroxide or potassium hydroxide.

[0015] In an exemplary embodiment, in step iii), the high-speed stirring time is 10 min, and the aluminum ion solution is an aluminum ion solution of aluminum sulfate or aluminum nitrate.

[0016] In an exemplary embodiment, in step iii), the heating temperature is 40-70° C., and the stirring time is 10-60 min.

[0017] In an exemplary embodiment, in step iii), the pH of the mixed solution is continuously adjusted using an alkaline substance, wherein the alkaline substance is aqueous ammonia, sodium hydroxide or potassium hydroxide, preferably aqueous ammonia.

[0018] The present application also provides an artificial stone product, which comprises the following components in percentage by mass:

[0019]

[0020] Wherein, the curing agent is a common unsaturated polyester curing agent, preferably one or more of methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl isobutyl ketone peroxide or benzoyl peroxide;

[0021] The promoter is cobalt naphthenate;

[0022] The defoamer is a defoamer suitable for unsaturated polyester, such as one or more of BYK-501, BYK-052, BYK-054, BYK-A550 or BYK-A555;

[0023] The color paste is a universal color paste for artificial stone.

[0024] In an exemplary embodiment, the artificial stone product comprises the following components in mass percentage:

[0025]

[0026] The present application also provides a method for preparing an artificial stone product, comprising:

[0027] 1) By mass, the following components in percentage by mass are mixed and stirred at high speed to obtain artificial stone slurry:

[0028]

[0029] 2) placing the artificial stone slurry in a vacuum box to evacuate the box and remove bubbles in the artificial stone slurry;

[0030] 3) pouring the artificial stone slurry into a model mold;

[0031] 4) After pouring, the mixture is allowed to stand and solidify, and the mold is demoulded to obtain a pre-cured artificial stone embryo;

[0032] 5) placing the pre-cured artificial stone body in an oven for heat preservation to obtain an artificial stone product.

[0033] In an exemplary embodiment, in step 2), the vacuuming time is 1 min.

[0034] In an exemplary embodiment, in step 3), the entire pouring process is completed on a vibration table.

[0035] In an exemplary embodiment, in step 4), the curing time is 60-360 minutes.

[0036] In an exemplary embodiment, in step 5), the temperature of the oven is 60-100° C., and the holding time is 60-480 min.

[0037] In an exemplary embodiment, the artificial stone product is a kitchen and bathroom countertop product, such as a basin.

[0038] Compared with the prior art solution (i.e., aluminum hydroxide powder-mixing-stirring-vacuum-casting-vibration degassing-precuring-demolding-curing-molding), the present application proposes a simple preparation method of glass fiber composite aluminum hydroxide, and uses the prepared composite material as an inorganic powder to compound with unsaturated polyester to obtain an artificial stone, which has the following technical effects:

[0039] 1. This application successfully prepared aluminum hydroxide coated glass fiber composite powder material by co-precipitation method;

[0040] 2. The present application uses the synthesized glass fiber aluminum hydroxide composite powder as an inorganic filler, and compounding it with unsaturated polyester for preparing artificial stone can significantly reduce the thermal expansion coefficient of artificial stone and improve the application range of artificial stone products.

[0041] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0043] Figure 1 This is a SEM image of the glass fiber composite aluminum hydroxide powder in Example 1 of the present application;

[0044] Figure 2 The artificial stone basin in Example 1 of the present application is seamlessly spliced ​​with a rock slab countertop;

[0045] Figure 3 The artificial stone basin in Comparative Example 1 is seamlessly spliced ​​with the rock slab countertop. DETAILED DESCRIPTION

[0046] The present application describes a plurality of embodiments, but the description is exemplary rather than restrictive, and it is apparent to those skilled in the art that there may be more embodiments and implementations within the scope of the embodiments described in the present application. Although many possible feature combinations are shown in the drawings and discussed in the specific embodiments, many other combinations of the disclosed features are also possible. Unless specifically limited, any feature of any embodiment may be used in combination with any other feature in any other embodiment, or may replace any other feature in any other embodiment.

[0047] A glass fiber composite aluminum hydroxide powder, wherein, by mass, the ratio of glass fiber to aluminum hydroxide is 10:1-1:6, and the length of the glass fiber is 0.1 mm-6 mm.

[0048] A method for preparing glass fiber composite aluminum hydroxide powder comprises mixing a glass fiber solution and an aluminum ion solution in an alkaline environment, and obtaining the glass fiber composite aluminum hydroxide powder after heating, stirring, filtering and drying.

[0049] In an exemplary embodiment, the preparation method includes: i) adding the glass fiber to deionized water and stirring to obtain a uniformly dispersed glass fiber solution; ii) adjusting the pH of the glass fiber solution to make it alkaline; iii) adding the aluminum ion solution to the glass fiber solution during high-speed stirring to obtain a mixed solution, heating and continuously stirring, while continuing to adjust the pH to be greater than 7; iv) filtering and drying the mixed solution to obtain the glass fiber composite aluminum hydroxide powder. The mass of the obtained glass fiber composite aluminum hydroxide powder is increased by 10%-500% compared with the initial glass fiber powder, that is, the mass ratio of glass fiber: aluminum hydroxide in the glass fiber composite aluminum hydroxide powder is 10:1-1:6.

[0050] In an exemplary embodiment, in step ii), an alkaline substance is added to the glass fiber solution to make the pH value of the glass fiber solution be 8-12, wherein the alkaline substance is ammonia water, sodium hydroxide or potassium hydroxide.

[0051] In an exemplary embodiment, in step iii), the high-speed stirring time is 10 min, the heating temperature is 40-70° C., the continuous stirring time is 10-60 min, and the aluminum ion solution is an aluminum ion solution of aluminum sulfate or aluminum nitrate.

[0052] In an exemplary embodiment, in step iii), the pH of the mixed solution is adjusted continuously using the alkaline substance, and the alkaline substance is aqueous ammonia, sodium hydroxide or potassium hydroxide, preferably aqueous ammonia.

[0053] An artificial stone product, comprising the following components in percentage by mass:

[0054]

[0055] Wherein, the curing agent is a common unsaturated polyester curing agent, such as one or more of methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl isobutyl ketone peroxide, and benzoyl peroxide;

[0056] The promoter is cobalt naphthenate;

[0057] The defoamer is a defoamer suitable for unsaturated polyester, such as one or more of BYK-501, BYK-052, BYK-054, BYK-A550 or BYK-A555;

[0058] The color paste is a general color paste for artificial stone, for example, one of the white paste RC69 or the black paste UP extra black of the DENSON brand of Dongguan or a combination thereof.

[0059] In an exemplary embodiment, the artificial stone product comprises the following components in mass percentage:

[0060]

[0061]

[0062] A method for preparing an artificial stone product, comprising:

[0063] 1) By mass, the following components in percentage by mass are mixed and stirred at high speed to obtain artificial stone slurry:

[0064]

[0065] 2) placing the artificial stone slurry in a vacuum box to evacuate the box and remove bubbles in the artificial stone slurry;

[0066] 3) pouring the artificial stone slurry into a model mold;

[0067] 4) After pouring, the mixture is allowed to stand and solidify, and the mold is demoulded to obtain a pre-cured artificial stone embryo;

[0068] 5) placing the pre-cured artificial stone body in an oven for heat preservation to obtain an artificial stone product.

[0069] In an exemplary embodiment, in step 2), the vacuuming time is 1 minute; in step 3), the entire pouring process is completed on a vibration table; in step 4), the curing time is 60-360 minutes; in step 5), the temperature of the oven is 60-100°C, and the insulation time is 60-480 minutes.

[0070] In an exemplary embodiment, the artificial stone product is a kitchen and bathroom countertop product, such as a basin.

[0071] Example 1.

[0072] 1) Preparation of glass fiber composite aluminum hydroxide powder

[0073] Weigh 1 kg of glass fiber powder, add it to 10 kg of deionized water, and evenly disperse it in the deionized water with a high-speed stirrer, then add a certain amount of ammonia water to the dispersion, adjust the pH of the dispersion to 11, continue high-speed stirring for 10 minutes, and then add 2 kg of aluminum sulfate to the dispersion, heat the solution to 60°C and continue stirring. During the continuous stirring process, the pH of the solution is continuously adjusted with ammonia water to ensure that the pH of the solution is greater than 7. After stirring for 60 minutes, the dispersion is filtered and dried to obtain glass fiber composite aluminum hydroxide powder.

[0074] 2) Mixing

[0075] By mass, the following raw materials were mixed and stirred at high speed for 10 minutes to obtain artificial stone slurry:

[0076]

[0077] Among them, the curing agent is methyl ethyl ketone peroxide, the accelerator is cobalt cyclohexaneate, the defoaming agent is BYK-A501, and the color paste is a combination of DENSON brand white paste RC69 and black paste UP extra black.

[0078] 3) Place the evenly mixed artificial stone slurry in a vacuum box and evacuate for 1 minute to remove bubbles in the artificial stone slurry.

[0079] 4) Pour the artificial stone slurry into the model mold, and the entire pouring process is completed on a vibration table.

[0080] 5) After pouring, the mold is left to solidify for 120 minutes, and then the mold is demoulded to obtain a pre-cured artificial stone embryo.

[0081] 6) The pre-cured artificial stone body was placed in an oven at 80° C. for 240 min to obtain an artificial stone basin sample.

[0082] Example 2.

[0083] 1) Preparation of glass fiber composite aluminum hydroxide powder

[0084] Weigh 1 kg of glass fiber powder, add it to 10 kg of deionized water, and evenly disperse it in the deionized water with a high-speed stirrer, then add a certain amount of sodium hydroxide to the dispersion, adjust the pH of the dispersion to 9, and then continue to stir at high speed for 10 minutes, then add 3 kg of aluminum nitrate to the dispersion, heat the solution to 50°C and continue stirring, and continuously adjust the pH of the solution with ammonia water during the stirring process to ensure that the pH of the solution is greater than 7. After stirring for 40 minutes, the dispersion is filtered and dried to obtain glass fiber composite aluminum hydroxide powder.

[0085] 2) Mixing

[0086] By mass, the following raw materials were mixed and stirred at high speed for 10 minutes to obtain artificial stone slurry:

[0087]

[0088] Among them, the curing agent is cyclohexanone peroxide, the accelerator is cobalt cyclohexaneate, the defoaming agent is BYK-054, and the color paste is a combination of DENSON brand white paste RC69 and black paste UP extra black.

[0089] 3) Place the evenly mixed artificial stone slurry in a vacuum box and evacuate for 1 minute to remove bubbles in the artificial stone slurry.

[0090] 4) Pour the artificial stone slurry into the model mold, and the entire pouring process is completed on a vibration table.

[0091] 5) After pouring, the mold is left to solidify for 120 minutes, and then the mold is demoulded to obtain a pre-cured artificial stone embryo.

[0092] 6) The pre-cured artificial stone body was placed in an oven at 80° C. for 240 min to obtain an artificial stone basin sample.

[0093] Example 3.

[0094] 1) Preparation of glass fiber composite aluminum hydroxide powder

[0095] Weigh 1 kg of glass fiber powder, add it to 10 kg of deionized water, and evenly disperse it in the deionized water with a high-speed stirrer, then add a certain amount of sodium hydroxide to the dispersion, adjust the pH of the dispersion to 11, and then continue to stir at high speed for 10 minutes, then add 3 kg of aluminum sulfate to the dispersion, heat the solution to 70°C and continue stirring, and continuously adjust the pH of the solution with ammonia water during the stirring process to ensure that the pH of the solution is greater than 7. After stirring for 40 minutes, the dispersion is filtered and dried to obtain glass fiber composite aluminum hydroxide powder.

[0096] 2) Mixing

[0097] By mass, the following raw materials were mixed and stirred at high speed for 10 minutes to obtain artificial stone slurry:

[0098]

[0099] Among them, the curing agent is methyl isobutyl ketone peroxide, the accelerator is cobalt cyclohexaneate, the defoaming agent is BYK-A555, and the color paste is a combination of DENSON brand white paste RC69 and black paste UP extra black.

[0100] 3) Place the evenly mixed artificial stone slurry in a vacuum box and evacuate for 1 minute to remove bubbles in the artificial stone slurry.

[0101] 4) Pour the artificial stone slurry into the model mold, and the entire pouring process is completed on a vibration table.

[0102] 5) After pouring, the mold is left to solidify for 120 minutes, and then the mold is demoulded to obtain a pre-cured artificial stone embryo.

[0103] 6) The pre-cured artificial stone body was placed in an oven at 80° C. for 240 min to finally obtain an artificial stone sample.

[0104] Comparative Example 1.

[0105] 1) Mixing

[0106] By mass, the following raw materials were mixed and stirred at high speed for 10 minutes to obtain artificial stone slurry:

[0107]

[0108] Among them, the curing agent is methyl ethyl ketone peroxide, the accelerator is cobalt cyclohexaneate, the defoaming agent is BYK-A501, and the color paste is a combination of DENSON brand white paste RC69 and black paste UP extra black.

[0109] 2) Place the evenly mixed artificial stone slurry in a vacuum box and evacuate for 1 minute to remove bubbles in the artificial stone slurry.

[0110] 3) Pour the artificial stone slurry into the model mold, and the entire pouring process is completed on a vibration table.

[0111] 4) After pouring, the mold is left to solidify for 120 minutes, and then the mold is demoulded to obtain a pre-cured artificial stone embryo.

[0112] 5) The pre-cured artificial stone body was placed in an oven at 80° C. for 240 min to finally obtain an artificial stone sample.

[0113] Experimental example 1.

[0114] The thermal expansion coefficients of the products of Examples 1-3 and Comparative Example 1 were tested, and the experimental results are shown in Table 1 below. The contents of the substances in Table 1 are the mass fractions of the substances in the total mass of the artificial stone products. As can be seen from Table 1, the artificial stone products prepared by the components and methods of the present application have a small thermal expansion coefficient and can meet the requirements of the product in the field.

[0115] Table 1

[0116]

[0117] Experimental example 2.

[0118] The quality of the basin products of Example 1 and Comparative Example 1 was tested, and the test results were shown in Table 2. As can be seen from Table 2, the artificial stone products prepared by the components and methods of the present application meet the technical requirements of the field.

[0119] Table 2

[0120]

[0121] The embodiments described in this application are exemplary rather than restrictive, and it is obvious to a person skilled in the art that there may be more embodiments and implementations within the scope of the embodiments described in this application.

Claims

1. A glass fiber composite aluminum hydroxide powder, wherein: By mass, glass fiber: aluminum hydroxide is 10:1-1:6; The length of the glass fiber is 0.1mm-6mm; The preparation of the glass fiber composite aluminum hydroxide powder comprises mixing a glass fiber solution and an aluminum ion solution in an alkaline environment, and obtaining the glass fiber composite aluminum hydroxide powder after heating, stirring, filtering and drying.

2. A method for preparing the glass fiber composite aluminum hydroxide powder according to claim 1, comprising: i) adding the glass fiber into deionized water and stirring to obtain a uniformly dispersed glass fiber solution; ii) adjusting the pH of the glass fiber solution to make it an alkaline aqueous solution; iii) adding the aluminum ion solution to the glass fiber solution under high-speed stirring to obtain a mixed solution, heating and continuously stirring, and continuously adjusting the pH to be greater than 7; iv) filtering and drying the mixed solution to obtain the glass fiber composite aluminum hydroxide powder.

3. The method according to claim 2, wherein in step ii), an alkaline substance is added to the glass fiber solution so that the pH of the alkaline aqueous solution is 8-12, wherein the alkaline substance is aqueous ammonia, sodium hydroxide or potassium hydroxide; in step iii), the high-speed stirring time is 10 minutes, the aluminum ion solution is an aluminum ion solution of aluminum sulfate or aluminum nitrate, the heating temperature is 40-70°C, and the continuous stirring time is 10-60 minutes.

4. The method according to claim 2, wherein in step iii), the pH of the mixed solution is adjusted by using an alkaline substance, wherein the alkaline substance is aqueous ammonia, sodium hydroxide or potassium hydroxide. The method according to claim 4 , wherein the alkaline substance is aqueous ammonia.

6. An artificial stone product comprising the following components in percentage by mass: Unsaturated polyester 20-40%; The method according to claim 1 Glass fiber composite aluminum hydroxide powder or The method according to any one of claims 2 to 5 in, The curing agent is a common unsaturated polyester curing agent; The promoter is cobalt naphthenate; The defoamer is a defoamer suitable for unsaturated polyester; The color paste is a universal color paste for artificial stone.

7. The artificial stone product according to claim 6, wherein: The curing agent is one or more of methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl isobutyl ketone peroxide or benzoyl peroxide.

8. The artificial stone product according to claim 6, wherein: The defoamer is one or more of BYK-501, BYK-052, BYK-054, BYK-A550 or BYK-A555.

9. The artificial stone product according to any one of claims 6 to 8, wherein: The artificial stone product is a kitchen and bathroom countertop product.

10. The artificial stone product according to claim 9, wherein: The artificial stone product is a basin.

11. A method for preparing the artificial stone product according to any one of claims 6 to 10, comprising: 1) By mass, the following components in percentage by mass are mixed and stirred at high speed to obtain artificial stone slurry: Unsaturated polyester 20-40%; The method according to claim 1 Glass fiber composite aluminum hydroxide powder or The method according to any one of claims 2 to 5 2) placing the artificial stone slurry in a vacuum box to evacuate the box and remove bubbles in the artificial stone slurry; 3) pouring the artificial stone slurry into a model mold; 4) After pouring, the mixture is allowed to stand and solidify, and the mold is demoulded to obtain a pre-cured artificial stone embryo; 5) placing the pre-cured artificial stone body in an oven for heat preservation to obtain an artificial stone product.

12. The method according to claim 11, in step 2), the vacuuming time is 1 min; In step 3), the entire pouring process is completed on a vibrating table; In step 4), the curing time is 60-360 min; In step 5), the temperature of the oven is 60-100° C., and the insulation time is 60-480 min.

13. An artificial stone product prepared according to the method of claim 11 or 12, wherein the artificial stone product is a kitchen and bathroom countertop product.

14. The artificial stone product according to claim 13, wherein: The artificial stone product is a basin.

Citation Information

Patent Citations

  • A kind of artificial stone and preparation method thereof

    CN104402309B

  • Anti-fouling and anti-cracking artificial marble and preparation method thereof

    CN113387616A

  • Formula and technological process of glass fiber product

    CN110171941A

  • Artificial Marble Chips, Artificial Marble Containing Same, and Production Method Therefor

    US20140350160A1